Composition and Anticandidal Activity of the Essential Oil of Hypericum perforatum L. - Alan, Sevim; Demirci, Betul; Iscan, Gokalp; Bulent Kose, Yavuz; Husnu Can Baser, Kemal (Asian Journal of Chemistry, 2010)
The essential oil obtained by hydrodistillation of Hypericum perforatum L. (Clusiaceae) obtained from Turkey was analyzed by gas chromatography and gas chromatography/mass spectrometry (GC/MS), simultaneously. Main constituents of the oil was found as germacrene D (23 %), β-caryophyllene (14 %), bicyclogermacrene (5 %), caryophyllene oxide (4 %) and spathulenol (4 %). The essential oil was also screened for its anticandidal properties against various Candida species.